Hagfishes of Mexico and Central America: Annotated catalog and identification key - Angulo Sibaja, Arturo (2016)
This catalogue contains revised and updated taxonomic and distributional information about hagfishes of Mexico and Central America (Pacific and Caribbean coasts). It includes all nominal species of the family Myxinidae known to be present in the area as well as contiguous waters (Galápagos Islands, West Indies, and the Colombian Pacific and Caribbean coasts). A total of three genera and 23 species are covered. Information under each species account includes: valid modern names and original citation of the species; popular, technical and/or vernacular names in English and Spanish; a brief description with distinctive characters; known distribution; documented records in Mexican and/or Central American waters (museum specimens); conservation status; major threats; literary references; and other pertinent taxonomic and ecological information. A key to the identification of the species also is provided.